2019
DOI: 10.1111/nep.13603
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐phosphate product and its impact on mortality in hospitalized patients

Abstract: Aim This study aimed to assess the relationship between admission Calcium‐phosphate (CaP) and in‐hospital mortality in hospitalized patients. Methods All adult hospitalized patients who had both admission serum calcium and phosphate levels available between years 2009 and 2013 were enrolled. Admission CaP was categorized based on its distribution into six groups (<21, 21–<27, 27–<33, 33  39, 39–<45 and ≥45 mg2/dL2). Multivariate logistic regression was used to assess the association between admission CaP and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…An increase in serum calcium is associated with incident heart failure [33] and possible hypercalcemia-induced neuronal injury among patients with acute ischemic stroke [34]. Moreover, an increase in serum calcium may result in AKI via renal vasoconstriction and nephrogenic diabetes insipidus-induced volume depletion [35][36][37][38][39][40]. In our current study, we also adjusted AKI during hospitalization in our multivariable logistic regression analysis, and we found that the upward trend of serum calcium change of >1.0 mg/dL was significantly associated with increased in-hospital mortality, while the highest mortality (6.3-fold increased mortality) was observed in patients with an absolute increase in serum calcium level ≥2.0 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in serum calcium is associated with incident heart failure [33] and possible hypercalcemia-induced neuronal injury among patients with acute ischemic stroke [34]. Moreover, an increase in serum calcium may result in AKI via renal vasoconstriction and nephrogenic diabetes insipidus-induced volume depletion [35][36][37][38][39][40]. In our current study, we also adjusted AKI during hospitalization in our multivariable logistic regression analysis, and we found that the upward trend of serum calcium change of >1.0 mg/dL was significantly associated with increased in-hospital mortality, while the highest mortality (6.3-fold increased mortality) was observed in patients with an absolute increase in serum calcium level ≥2.0 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Serum phosphate levels have been identified as strong predictors on clinical outcomes, including hospital mortality [4]. While hypophosphatemia is shown to be independently associated with increased mortality among critically ill patients, malnourished individuals, and patients with sepsis [5][6][7], hyperphosphatemia is associated with poor clinical outcomes including mortality in chronic kidney disease (CKD) [8,9], hemodialysis [10,11], acute coronary syndrome [12], and general patient population [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Post-KTx hypophosphatemia is known to be associated with lower risks of death-censored graft failure and cardiovascular mortality [ 85 ]. The association between post-KTx hypophosphatemia and reduced cardiovascular mortality among KTx recipients could be related to the reduction of calcium phosphate product, an important factor associated with vascular calcification and cardiovascular events [ 98 , 99 ]. Our study demonstrated that successful KTx can result in a significant increase in serum klotho levels among KTx recipients [ 85 ].…”
Section: Discussionmentioning
confidence: 99%